Ginzburg–Landau expansion in BCS–BEC crossover region of disordered attractive Hubbard model - Kuchinskii, E.Z.; Kuleeva, N.A.; Sadovskii, M.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
We have studied disorder effects on the coefficients of Ginzburg–Landau expansion for attractive Hubbard mod-el within the generalized DMFT+Σ approximation for the wide region of the values of attractive potential U — from the weak-coupling limit, where superconductivity is described by BCS model, towards the strong coupling, where superconducting transition is related to Bose–Einstein condensation (BEC) of compact Cooper pairs. For the case of semi-elliptic initial density of states disorder influence on the coefficients A and B before the square and the fourth power of the order parameter is universal for at all values of electronic correlations and is related only to the widening of the initial conduction band (density of states) by disorder. Similar universal behavior is valid for superconducting critical temperature Tc (the generalized Anderson theorem) and specific heat discontinuity at the transition. This universality is absent for the coefficient C before the gradient term, which in accordance with the standard theory of “dirty” superconductors is strongly suppressed by disorder in the weak-coupling region, but can slightly grow in BCS–BEC crossover region, becoming almost independent of disorder in the strong coupling region. This leads to rather weak disorder dependence of the penetration depth and coherence length, as well as the slope of the upper critical magnetic field at Tc, in BCS–BEC crossover and strong coupling regions.